Optimization of Chalcopyrite Galvanic Leaching in the Presence of Pyrite and Silver as Catalysts by using Response Surface Methodology (RSM) (Rudarsko-geološko-naftni zbornik, 2021)
In this research, dissolution of chalcopyrite concentrate is modelled and optimized using Response Surface Methodology (RSM). Also, effective parameters in the leaching process such as the amount of pyrite, silver ions, redox potential and initial concentration of acid are comprehensively studied. Central Composite Design (CCD) methodology is chosen as the design matrix to predict the optimum level of the parameters. In the next step, it will be proven that in the presence of silver ions, pyrite effectiveness is improved and also the chalcopyrite dissolution rate is increased considerably. Using the result of quadratic programming, a rotation speed of 1000 rpm, a pyrite/chalcopyrite mass ratio of 3:1, the amount of 150 ppm silver ion, a solution potential set point of 470 mV, at 800°C and 25 g/L initial acid concentration are the optimal level of the selected parameters wherein the maximum copper extraction with more than 95% in less than 10 hours can be accessible.